2013
DOI: 10.4018/jkm.2013040103
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation into the Influence of Knowledge Sharing Barriers on Knowledge Sharing and Individual Innovation Behaviour

Abstract: Knowledge sharing barriers reduce the propensity of individuals to share knowledge and produce innovation behaviour. Thus, identifying barriers and their impact on knowledge sharing and individual innovation behaviour is a potential research area to study. Considering lack of studies in the literature, this study provides further evidence regarding the implications of knowledge sharing barriers in the workplace. Data was collected from eighty three academic staff in a higher education institution and analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 57 publications
2
21
2
1
Order By: Relevance
“…this is in contrast to research conducted by the Yesil (2013) who studied the effect of the dimensions of knowledge sharing which includes collecting and donating knowledge of the behavior of the innovation of human resources in Turkey and found that both these dimensions did not significantly influence the innovation capabilities of human resources.…”
Section: Introductioncontrasting
confidence: 51%
See 3 more Smart Citations
“…this is in contrast to research conducted by the Yesil (2013) who studied the effect of the dimensions of knowledge sharing which includes collecting and donating knowledge of the behavior of the innovation of human resources in Turkey and found that both these dimensions did not significantly influence the innovation capabilities of human resources.…”
Section: Introductioncontrasting
confidence: 51%
“…By having the ability to innovate is high then the organization can ensure the progress of the organization and enable the creation of a sustainability organization for innovation can have a significant impact on the economic performance and financial organizations (Marques & Ferreira, 2009). Yesil (2013) stated that the desire and capability of human resources for innovation can ensure the flow of innovation within the organization. Various studies in the literature to believe in the importance of the innovative work behaviors owned human resources for the performance and sustainability of the organization (Yesill, 2013).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, academicians and researchers are trying to fully understand different dimensions of KM, its potential applications and benefits to different types of organizations, including educational institutions. Among other KM topics, information and (Sharma, Singh & Neha, 2012;Yeşil & Hırlak, 2013). Many of these studies have also revealed that the major barriers to sharing are mind-set and unwillingness of individuals to share their knowledge due to a multitude of reasons (Riege, 2005;Khalil & Shea, 2012).…”
Section: Knowledge Sharing and Learning Processmentioning
confidence: 96%